STE20-type kinase TAOK3 regulates hepatic lipid partitioning - Ying Xia; Mara Caputo; Emmelie Cansby; Sumit Kumar Anand; Silva Sütt; Marcus Henricsson; Rando Porosk; Hanns-Ulrich Marschall; Matthias Blüher; Margit Mahlapuu (Elsevier, 2021)
Objective: Nonalcoholic fatty liver disease (NAFLD), defined by excessive lipid storage in hepatocytes, has recently emerged as a leading global cause of chronic liver disease. The aim of this study was to examine the role of STE20-type protein kinase TAOK3, which has previously been shown to associate with hepatic lipid droplets, in the initiation and aggravation of human NAFLD. Methods: The correlation between TAOK3 mRNA expression and the severity of NAFLD was investigated in liver biopsies from 62 individuals. In immortalized human hepatocytes, intracellular fat deposition, lipid metabolism, and oxidative and endoplasmic reticulum stress were analyzed when TAOK3 was overexpressed or knocked down by small interfering RNA. Subcellular localization of TAOK3 was characterized in human and mouse hepatocytes by immunofluorescence microscopy. Results: We found that the TAOK3 transcript levels in human liver biopsies were positively correlated with the key lesions of NAFLD (i.e., hepatic steatosis, inflammation, and ballooning). Overexpression of TAOK3 in cultured human hepatocytes exacerbated lipid storage by inhibiting β-oxidation and triacylglycerol secretion while enhancing lipid synthesis. Conversely, silencing of TAOK3 attenuated lipid deposition in human hepatocytes by stimulating mitochondrial fatty acid oxidation and triacylglycerol efflux while suppressing lipogenesis. We also found aggravated or decreased oxidative/endoplasmic reticulum stress in human hepatocytes with increased or reduced TAOK3 levels, respectively. The subcellular localization of TAOK3 in human and mouse hepatocytes was confined to intracellular lipid droplets. Conclusions: This study provides the first evidence that hepatic lipid droplet-coating kinase TAOK3 is a critical regulatory node controlling liver lipotoxicity and susceptibility to NAFLD.